How to report E-values for meta-analyses: Recommended improvements and additions to the new GRADE approach. (February 2022) - Mathur, Maya B.; VanderWeele, Tyler J.
Abstract: In a recent concept paper (Verbeek et al., 2021), the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) Working Group provides a preliminary proposal to improve its existing guidelines for assessing sensitivity to uncontrolled confounding in meta-analyses of nonrandomized studies. The new proposal centers on reporting the E-value for the meta-analytic mean and on comparing this E-value to a measured "reference confounder" to determine whether residual uncontrolled confounding in the meta-analyzed studies could or could not plausibly explain away the meta-analytic mean. Although we agree that E-value analogs for meta-analyses could be an informative addition to future GRADE guidelines, we suggest improvements to the Verbeek et al. (2021)'s specific proposal regarding: (1) their interpretation of comparisons between the E-value and the strengths of associations of a reference confounder; (2) their characterization of evidence strength in meta-analyses in terms of only the meta-analytic mean; and (3) the possibility of confounding bias that is heterogeneous across studies.